Courting justice : ten New Jersey cases that shook the nation - Tractenberg, Paul L., 1938- (Rivergate regionals., 2013)
Ten cases decided between 1960 and 2011, including the Karen Ann Quinlan decision, the Baby M case, the Mount Laurel decision, Megan's Law, and the series of decisions known as Abbott/Robinson that directed state funding of poor urban schools on par with suburban districts, shed light on landmark decisions and their impact on national and global events. Different experts cover each case, providing insight into the court's approach and decision-making process.